Solving the Problem of Profit Maximization in Najwa Sewing House Textile Business in Salatiga - Hutauruk, Stefany Margaretha; Pitaningtyas, Farisca Ayu; Albar, Wakhid Fitri; Hidayat, Agus Sofian Eka (Mathematical Journal of Modelling and Forecasting, 2023)
Linear programs are often referred to as linear problem-solving methods, one of which is the simplex method. The simplex method is an approach that the author can use in solving a linear program problem in determining the optimal solution that has two or more decision variables where in determining the combination itself can be repeated iterating over the simplex table until the optimum value is found in the optimization problem that has been studied. The business world must have optimization problems that include maximum profits and minimum costs where both problems can be solved using the simplex method. The research began on May 14, 2023 at Najwa Sewing House (Clothing Store) Ngelosari, Jombor, Kec.Tuntang, Semarang Regency. The purpose of this study is to describe and analyze the simplex method in a linear program so that maximum profit is obtained in the production of Najwa Sewing House. The analysis carried out in this study is an analysis using the simplex method with calculations assisted by excel applications. The results showed that the amount of optimum production from each product capacity at Najwa Sewing House resulted in a maximum profit of IDR 2.550.000.